Population Viability Analysis of the Endangered Roan Antelope in Ruma National Park, Kenya, and Implications for Management - Johnstone K. Kimanzi (The Scientific World Journal)
Population viability analysis (PVA) was used to (1) establish causes of roan population decline for the past 30 years in Ruma National Park (RNP), the only park where wild roans remain in Kenya, and (2) predict the probability of roan persistence under existing and alternative management options. PVA was done using long-term data based on population dynamics, life history, climatic conditions, and expert knowledge. Poaching was identified as the main cause of roan decline in RNP. Several antipoaching and prioritized habitat management interventions to promote population recovery and sustainable conservation of roans are described. PVA predictions indicated that, without these interventions, the roan population cannot persist more than 3 decades. Furthermore, ensuring sustainable conservation of roans in RNP will boost tourism in Western Kenyan and thus alleviate poverty in this part of the country. Improved income from tourism will reduce the possible pressures from hunting and give greater incentives for local people to be actively engaged in roan conservation.